Skeptical erections - Sapeta, Mxolisi (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2017)
This collection of poems is an interrogation of the self - turbulent urban experiences, fear, betrayal, mistrust, unfulfilled sexual desires - made with plain language, truthfulness, subtlety and humour. The poems are reflections of New Brighton township where the poet was born, they mirror his experiences of family life, the streets and the juxtaposed characters he encountered as an artist, drinking partner and lover. These experiences shift between broken family lives, passionate short-lived romances, heated artists' debates during gallery exhibitions, shebeens and dangerous midnight homecomings between cruel thugs and greedy whores and all those who clutter the shebeens and the streets at night. The poems reflect all facets of these experiences - including imagination, emotion, and fantasy. At times grammar and syntax are sacrificed in order to get to the emotion. The collection draws strong inspiration from the Peruvian poet Cesar Vallejo -- with his clear-cut graphic imagery and sincere morbid undertone, he is unquestionably true to his vision of life. This also applies tothe work of Tchicaya U Tam'si, Blas de Otero, Dambuzo Marechera and Roque Dalton, who have all been influences.
Keywords: Uncatalogued